Contribution of Woldemar von Knieriem to the Training and Experimental Farm «Peterhof» of Riga Polytechnicum and Riga Polytechnic Institute - Kovaļčuka, Svetlana (History of Engineering Sciences and Institutions of Higher Education, 2019)
The article is dedicated to Professor Woldemar von Knieriem (1849– 1935), who has made a significant contribution to the development of agricultural science, headed the Department of Agriculture of Riga Polytechnic Institute (1903–1906), as well as Training and Experimental Farm «Peterhof» (1880– 1915) near Olaine city. It became a model farm not only in the Baltic region but also throughout the Russian Empire. Professor W. von Knieriem was the Director of RPI (1906–1916), an outstanding organizer and author of scientific works. He provided students with extensive theoretical and practical knowledge in agriculture, focusing on practical, scientifically approbated lessons about the management of agricultural land and manors and trying to raise the general level of culture and the horizons of young people. Professor W. von Knieriem was Rector of the Baltic Technical University in Riga (1918) and worked in the Herder Institute in Riga (1920–1927). He spent his last years in his family estate in Livonia writing memories of his life and enjoying the company of grandchildren – one of them later became Prime Minister of Sweden Ulof Palme (1927–1986). W. von Knieriem died in January 1935 and was buried in the Great Cemetery in Riga.